2022
DOI: 10.1371/journal.pone.0271616
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in UCA1, a lncRNA functioning as a miRNA sponge, determine endometriosis development and the potential associated infertility via regulating lipogenesis

Abstract: Endometriosis is a hormone-associated disease which has been considered as the precursor for certain types of ovarian cancer. In recent years, emerging evidence demonstrated potent roles of lncRNA in regulating cancer development. Since endometriosis shares several features with cancer, we investigated the possible involvement of cancer-related lncRNAs in endometriosis, including UCA1, GAS5 and PTENP1. By using massARRAY system, we investigated certain genetic variations in cancer-related lncRNAs that can chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In their observational study, Crescioli et al found that the SNPs of IL6 (rs1800797) and TNF (rs1800629) may serve as possible indicators of baseline pain severity and opioid dosage requirements among pediatric cancer patients [ 40 ]. In a pioneer study, Chang et al investigated the putative participation of cancer-related lncRNAs in endometriosis and detected genetic variants in UCA1, a lncRNA serving as a miRNA sponge, which can be found in endometriosis development and is potentially associated with infertility via regulating lipogenesis [ 101 ]. Satkunananthan et al conducted a review to assess the polymorphism associations with variability in opioid therapy responses in Asian cancer pain patients.…”
Section: Discussionmentioning
confidence: 99%
“…In their observational study, Crescioli et al found that the SNPs of IL6 (rs1800797) and TNF (rs1800629) may serve as possible indicators of baseline pain severity and opioid dosage requirements among pediatric cancer patients [ 40 ]. In a pioneer study, Chang et al investigated the putative participation of cancer-related lncRNAs in endometriosis and detected genetic variants in UCA1, a lncRNA serving as a miRNA sponge, which can be found in endometriosis development and is potentially associated with infertility via regulating lipogenesis [ 101 ]. Satkunananthan et al conducted a review to assess the polymorphism associations with variability in opioid therapy responses in Asian cancer pain patients.…”
Section: Discussionmentioning
confidence: 99%
“…UCA1 can interact with various miRNAs, which then change gene expression profiles and control tumor progression. The participation of genetic variants of UCA1 in the development of endometriosis and related infertility is indicated [ 26 ].…”
Section: Discussionmentioning
confidence: 99%